Gendered dimensions of improved agricultural practices in farm households in a coastal polder of southwest Bangladesh - Haque, Sadika; Aktar, Nasiba; Khan, M. Sahed (Bangladesh Agricultural University, 2023)
Gender disparities persist in farm households in the climate-vulnerable coastal Bangladesh. Keeping this view in mind, this study explored the intrahousehold gendered dimensions in some coastal polders of southwest Bangladesh. A stratified random sampling method was employed to select 350 farm households from the polder 30 under Khulna district. Different quantitative descriptive and statistical techniques have been followed here. The study found that among the cropping patterns, Rice–Fallow, HYV Rice–Sesame and HYV Rice–Mungbean were the most dominant cropping patterns, and the introduction of improved cropping patterns resulted in an increase in women’s workload. Most of the decisions regarding production methods, variety selection, and marketing were taken primarily by men (guided by cultural norms), but women had huge workload of postharvest operations, and greater involvement in household chores. The study identified that household heads’ engagement in the nonagriculture sector, women’s paid employment outside the households, farm size, household size and their existing knowledge are factors influencing women’s decision-making and bargaining power. It seems when men are involved in nonagriculture, women participate more in farm works, they take more decisions and their level of bargaining power increases. Again, women’s employment in paid work made them more empowered. So, the same women participate in agriculture for the household and other paid work, achieve bargaining power and are able to take decisions on production. What about time management? It is a matter of concern, whether women’s position at household is traded off with their workload. In conclusion, this study provides strategic gender-focused policy recommendations.